A new excavation technology of blasting combined with TBM. Issue 1 (1st January 2021) - Man, Ke; Liu, Xiaoli; Song, Zhifei
Abstract: The technical feasibility of drilling and blasting or TBM excavation method is the key to determine the underground engineering. In view of the high strength, high abrasiveness and good integrity of hard rock in site, and considering the damage of surrounding rock must be controlled within a reasonable range, the blasting combined with TBM method has been proposed here. While the combined method has been further carried out in Water Supply Project in Jilin to assess and evaluate it, which including single-hole blasting, five-hole blasting, eleven-hole blasting and blasting combined with TBM tests. It is found that some certain blasting tests is useful and essential to the combined method, as it can provide the blasting parameters designed for the combined method. The blasting of multi-hole simultaneous initiation with interval charge structure should be adopted strictly. Meantime, one roll of explosive in each blasting hole can produce obvious blasting phenomenon. Simultaneously, by means of vibration monitoring, borehole TV observation and sound wave measurement, it can be judged that the damaged degree is rather small. After pre-blasting, the average speed of TBM driving is 17.41 mm/min, increased by 42.3% than that of the previous cycle. It shows that the new method not only achieves a relative efficient excavation, but also rock damage has been controlled. Moreover, the shortcomings of low speed and high tool wear of TBM excavation in hard rock could be avoided and the excavation efficiency could be improved using the combined method. Therefore, it seems to be a practical technology, which can play full advantages of each existed method, while can avoid the defects of themselves. However, this new excavation technology needs further confirmation through more engineering verification. The results obtained in this paper have guiding significance and promising application in the underground excavation and other civil engineering.